1973
DOI: 10.1159/000230964
|View full text |Cite
|
Sign up to set email alerts
|

Heterophile Antigen Detected by Infectious Mononucleosis Sera on Lymphoid Cells

Abstract: In extending previous studies, it was shown that not only malignant but also normal murine lymphoid cells contain the heterophile antigen combining with infectious mononucleosis (IMS) sera. Evidence was presented, however, that malignant lymphoid cells contain heterophile antigen at a higher density and possibly in a more ‘complete’ form than normal lymphoid cells. Nonlymphoid nucleated murine cells contain very little, if any, heterophile antigen. Distribution of heterophile antigen in normal rat tissues is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1973
1973
1981
1981

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…Our previous studies [13,23,24] showed that P-B antigen was expressed pre dominantly on murine thymocytes and T cell lymphomas as well as on neutrophilic granulocytes in rat bone marrow. In accord ance with these results, BS and B antigens were extracted from murine thymus and spleen but not erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies [13,23,24] showed that P-B antigen was expressed pre dominantly on murine thymocytes and T cell lymphomas as well as on neutrophilic granulocytes in rat bone marrow. In accord ance with these results, BS and B antigens were extracted from murine thymus and spleen but not erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…This was performed as a test for hemolysis in agar gel following the previously described procedure [2,4]. In brief, one volume of a 1.25-percent suspension of BRBC (v/v) was mixed at 43 °C with six volumes of 1% Difco Bacto agar containing DEAE dextran at a concentration of 0.5°/o (w/v).…”
Section: Methodsmentioning
confidence: 99%
“…Absorption studies brought clear-cut evidence that the observed results were due to the reactions of heterophile antibodies in IM sera with the heterophile an tigen present on malignant murine lymphoid cells which in all instances were of T cell origin. Further studies showed that normal murine thymo-cytes and splenocytes but not other cells contain the heterophile antigen [4], Comparative absorption experiments indicated that the heterophile antigen on normal murine lymphoid cells has lower density and/or ap pears in less complete form than on malignant lymphoid cells [4].…”
Section: Introductionmentioning
confidence: 99%
“…The absorption efficacy of the bone marrow cells was quite analogous to that of murine thymocytes which were shown to possess P-B antigen in our previous studies [8,9]. Finally, relationship between P-B antigen and Fc receptor sites on mu rine bone marrow cells was studied by means of blocking experiments [6].…”
Section: Resultsmentioning
confidence: 55%
“…It was found that oxen possess the heterophile [Paul-Bunnell (P-B)] antigen not only on erythrocytes but also on all cells thus far examined including cells of kidney [7], aortic intima, adrenal and spleen [5], as well as platelets [14], Of particular interest was the distribution of P-B antigen in murine lymphoid cells: thymocytes as well as Thy-1 positive lymphoma cells have been shown to possess the antigen [8,9], while the antigen could not be detected on spleen cells of nude mice [unpublished data]. It was, there fore, concluded that the P-B antigen is a marker for murine T lympho cytes.…”
Section: Introductionmentioning
confidence: 99%